2009
DOI: 10.1242/jeb.022780
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Presenilin 1 (PS1) levels in senescence-accelerated mice(SAMP8) may indirectly impair memory by affecting amyloid precursor protein(APP) processing

Abstract: SUMMARYSenescence-accelerated mice (SAMP8) serve as a model for Alzheimerʼs disease (AD) as they exhibit early loss of memory and increased amyloid precursor protein (APP) expression. APP is a ubiquitous membrane protein that is physiologically processed by site-specific proteolysis firstly by α-or β-secretases, releasing a large fragment called APP S that contains most of the extracellular sequences of APP, a small extracellular stub, the transmembrane region and the cytoplasmic tail of APP (ʻAICDʼ-APP intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
2
28
0
1
Order By: Relevance
“…The data also shed light on the fact that the overexpression of human PS1 triggers synaptic dysfunction at older ages. Recently, Kumar et al (2009) reported that PS1 expression increased with age in senescence-accelerated mice, which might serve as a model for AD. It has also been shown that PS1 is highly expressed both during normal aging and in brains developing sporadic AD (Miller et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data also shed light on the fact that the overexpression of human PS1 triggers synaptic dysfunction at older ages. Recently, Kumar et al (2009) reported that PS1 expression increased with age in senescence-accelerated mice, which might serve as a model for AD. It has also been shown that PS1 is highly expressed both during normal aging and in brains developing sporadic AD (Miller et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, wild-type PS1 overexpression alone, which does not lead to A␤ hypersecretion, has never been reported to have major pathological manifestations in young animals. Although the long term effects of wild-type human PS1 overexpression have never been analyzed, a growing body of evidence suggests that PS1 expression level during both normal and pathological aging may play an important role (Miller et al, 2008;Kumar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The nucleotide sequence of APP in the hippocampus of SAMP8 does not have mutations similar to those that have been reported in human familial AD (4). Moreover, the SAMP8 PS1 cDNA sequence is identical to that of normal mice (5). The SAMP8 is characterized by an earlier onset of deficits in learning and memory than the normally aging mice, SAMR, in several tasks such as active and passive avoidance, Tmaze, and water maze tasks (6 -8).…”
Section: Introductionmentioning
confidence: 88%
“…PS1 has been shown to play a critical role in facilitating γ-secretase activity, and levels of γ-secretase modulate the Aβ 42 /Aβ 40 ratio, which is important for plaque formation [80]. Moreover, mutations in this protein are associated with familial AD (FAD).…”
Section: Histopathological Similarities In Samp8 and Admentioning
confidence: 99%